2015
DOI: 10.1002/app.42890
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing techniques on the 3D microstructure of poly (l‐lactic acid) scaffolds reinforced with wool keratin from different sources

Abstract: The aim of this work was the analysis of morphologies of poly (l‐lactic acid)/keratin tridimensional scaffolds developed by using two main solvent based techniques: solvent casting particulate leaching in the presence of paraffin microspheres as porogen, and thermally induced phase‐separation process. Keratins from different sources were used. Specifically, keratin from Merino wool (KM) and Brown Alpaca (KA) were dispersed in dioxane or 1,4‐dioxane/water mixture and then the keratin structure after interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Aiming to produce scaffolds for favourable distribution of biological molecules and cell ingrowth, the same authors used the same keratin sources (Merino wool and Brown Alpaca fibres) to produce biocompatible PLLA/keratin tridimensional scaffolds via two methods, namely solvent casting followed by porogen (paraffin) particulate leaching, and a thermally induced phase-separation process. The authors reported that the scaffolds porosity and architecture were highly sensitive to the porogen content and solvent/non-solvent ratio, allowing the formation of a variety of microcellular and porous foam morphologies [186]. Also using wool keratin, Li et al [187] produced hydroxyapatite (HA) in situ into a wool keratin solution and electrospun together with poly(L-lactic) acid (PLLA), forming a fibrous membrane.…”
Section: Polyvinyl Alcohol (Pvoh)mentioning
confidence: 99%
“…Aiming to produce scaffolds for favourable distribution of biological molecules and cell ingrowth, the same authors used the same keratin sources (Merino wool and Brown Alpaca fibres) to produce biocompatible PLLA/keratin tridimensional scaffolds via two methods, namely solvent casting followed by porogen (paraffin) particulate leaching, and a thermally induced phase-separation process. The authors reported that the scaffolds porosity and architecture were highly sensitive to the porogen content and solvent/non-solvent ratio, allowing the formation of a variety of microcellular and porous foam morphologies [186]. Also using wool keratin, Li et al [187] produced hydroxyapatite (HA) in situ into a wool keratin solution and electrospun together with poly(L-lactic) acid (PLLA), forming a fibrous membrane.…”
Section: Polyvinyl Alcohol (Pvoh)mentioning
confidence: 99%
“…It should be used for niche applications. In our research activities we used the solvent-based approach mainly when we dispersed a small amount of synthesized nanoparticles in a polymer soluble in organic solvent, and also in the case of solvent-stable soluble nanoparticles [ 9 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, important points are also to avoid the adverse effects on the polymer. A variety of processing techniques can be exploited to develop dense polymer nanocomposite films [10][11][12][13]38,64] or three-dimensional porous structures [65,66]. The selection of the processing method depends on the type of biopolymer, on the nanoparticle, and the final application.…”
Section: Nanocomposite Processingmentioning
confidence: 99%